Preclinical studies of the combined ointment based on walnut extract - Mozhaiev , Ivan; Nosalska, Tetyana; Dovha , Inna; Yevsiukova , Victoria; Kazmirchuk , Victor (Annals of Mechnikov's Institute, 2024)
Currently, the treatment of wound infection and its complications is an urgent problem in medicine. Gunshot and shrapnel injuries are characterized by the greatest severity, multiple, combined and multi-component nature of damage. In this regard, much attention is paid to the development and use of antimicrobial agents for the local treatment of purulent-inflammatory processes, primarily based on plant extracts. The advantage of using medicinal plants and phytopreparations in medical practice is their low toxicity and absence of pronounced side effects. A combined medicinal product for the treatment of wound infection in the form of an ointment based on plant raw materials - extracts of black walnut or walnut, antiseptic miramistin and anesthetic lidocaine hydrochloride has been developed at the State University "IMI NAMN of Ukraine". It is known that the toxicity, as well as the biological activity, of walnut extracts is due to their main active component - juglone. In vitro experiments have shown that juglone has a cytotoxic effect, causing the destruction of cell membranes. At the same time, when applied to the skin, juglon is poorly absorbed, so its systemic effects and manifestations of toxicity are unlikely. In this regard, a study of the harmlessness of the developed composition of the ointment with walnut carbonic acid extract (EGV) was conducted. The study was performed on outbred white rats in accordance with methodological recommendations for the experimental study of the toxic effect of potential medicinal products. It was established that the combined ointment based on walnut extract with carbonic acid does not have a negative effect on the body of experimental animals, does not affect biochemical and hematological indicators, when used once or chronically. In addition, the ointment does not have a local irritating effect when applied chronically. Thus, the obtained results of the harmlessness study allow us to conclude that the combined ointment based on carbonic walnut extract is completely safe in terms of acute and chronic toxicity, as well as local irritant effect. Key words: walnut carbonicum extract, acute toxicity, chronic toxicity, local irritant effect.